Integrated Front End Electronics Design for Micromachined Ultrasound Transducers - Vanagas, G.; Viržonis, D.; Paukštaitis, V.; Baranauskas, D.; Červiakov, S. (Elektronika ir Elektrotechnika, 2010)
Chip level integration of two dimensional (2D) capacitive micromachined ultrasound transducer (CMUT) array with custom integrated circuit (IC) for the real-time three dimensional (3D) medical imaging is described. Front-end electronics IC contains 4096 pulsers, producing 50 V pulses and 4096 low noise 12 MHz band preamplifiers with switches. 256 multiplexers, having 16 outputs each are used for readout of the signal from transducer elements. This scheme enables the control of transducer apertures containing 256 elements for transmit and receive.